Photochromic properties of composite films of thermally irreversible diarylethenes and fulgimides in polytetrafluoroethylene matrix - Kobeleva, O.I.; Valova, T.M.; Ait, A.O.; Barachevsky, V.A.; Grytsenko, K.P.; Machulin, V.F.; Krayushkin, M.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Photochromic polymeric thin films have been prepared by vacuum codeposition of polytetrafluoroethylene (PTFE) and thermally irreversible photochromic compounds: the cyclopentene derivative of diarylethene and fulgimide. Their photochromic properties were studied using the spectral-kinetic method as compared with polymethyl methacrylate (PMMA) films filled with the same photochromic compounds prepared using the spin coating method. The films prepared using codeposition in vacuum are characterized by photochromic properties acceptable for recording media for 3D optical memory